Tumor in 3D: In Vitro Complex Cellular Models to Improve Nanodrugs Cancer Therapy - Fernandes, Soraia; Cassani, Marco; Pagliari, Stefania; Filipensky, Petr; Cavalieri, Francesca; Forte, Giancarlo (Current medicinal chemistry, 2020)
Nanodrugs represent novel solutions to reshuffle repurposed drugs for cancer therapy. They might offer different therapeutic options by combining targeted drug delivery and imaging in unique platforms. Such nanomaterials are deemed to overcome the limitations of currently available treatments, ultimately improving patients' life quality. However, despite these promises being made for over three decades, the poor clinical translation of nanoparticle- based therapies calls for deeper in vit.. and in vivo investigations. Translational issues arise very early during the development of nanodrugs, where complex and more reliable cell models are often replaced by easily accessible and convenient 2D monocultures. This is particularly true in the field of cancer therapy. In fact, 2D monocultures provide poor information about the real impact of the nanodrugs in a complex living organism, especially given the poor mimicry of the solid Tumors Microenvironment (TME). The dense and complex extracellular matrix (ECM) of solid tumors dramatically restricts nanoparticles efficacy, impairing the successful implementation of nanodrugs in medical applications. Herein, we propose a comprehensive guideline of the 3D cell culture models currently available, including their potential and limitations for the evaluation of nanodrugs activity. Advanced culture techniques, more closely resembling the physiological conditions of the TME, might give a better prediction of the reciprocal interactions between cells and nanoparticles and eventually help reconsider the use of old drugs for new applications.
Keywords: drug delivery; nádorové mikroprostředí; Pharmaceutical Preparations; Neoplasms; Nanostructures; Nanoparticles; nanočástice; nanostruktury; nanomedicine; physiological conditions; léčivé přípravky; Drug Delivery Systems; 3D in vitro cell models; lidé; Humans; tumor; nádory; Tumor Microenvironment; lékové transportní systémy; Nanodrugs